The timing and cause of glacial activity during the last glacial in central Tibet based on 10Be surface exposure dating east of Mount Jaggang, the Xainza range. (15th April 2018) - Dong, Guocheng; Zhou, Weijian; Yi, Chaolu; Fu, Yunchong; Zhang, Li; Li, Ming
Abstract: Mountain glaciers are sensitive to climate change, and can provide valuable information for inferring former climates on the Tibetan Plateau (TP). The increasing glacial chronologies indicate that the timing of the local Last Glacial Maximum (LGM) recorded across the TP is asynchronous, implying different local influences of the mid-latitude westerlies and Asian Summer Monsoon in triggering glacier advances. However, the well-dated sites are still too few, especially in the transition zone between regions controlled by the two climate systems. Here we present detailed last glacial chronologies for the Mount Jaggang area, in the Xainza range, central Tibet, with forty-three apparent 10 Be exposure-ages ranging from 12.4 ± 0.8 ka to 61.9 ± 3.8 ka. These exposure-ages indicate that at least seven glacial episodes occurred during the last glacial cycle east of Mount Jaggang. These include: a local LGM that occurred at ∼61.9 ± 3.8 ka, possibly corresponding to Marine Isotope Stage 4 (MIS 4); subsequent glacial advances at ∼43.2 ± 2.6 ka and ∼35.1 ± 2.1 ka during MIS 3; one glacial re-advance/standstill at MIS3/2 transition (∼29.8 ± 1.8 ka); and three glacial re-advances/standstills that occurred following MIS 3 at ∼27.9 ± 1.7 ka, ∼21.8 ± 1.3 ka, and ∼15.1 ± 0.9 ka. The timing of these glacial activities is roughly in agreement with North Atlantic millennial-scale climate oscillations (Heinrich events), suggesting the potential correlations between these abrupt climate changes and glacial fluctuations in the Mount Jaggang area. The successively reduced glacial extent might have resulted from an overall decrease in Asian Summer Monsoon intensity over this timeframe. Highlights: 10 Be ages constrain seven glacial events east of Mount Jaggang during the last glacial. The local LGM likely corresponds to MIS 4. Two MIS 3 advances and four following re-advances/standstills are identified. North Atlantic climatic oscillations play a major role in driving these glacial events.